Smart arbitration system for multiprocessor AMBA interface in system on chip - Rokon, M. I. R.; Motakabber, S. M. A.; Alam, A. H. M. Zahirul; Habaebi, Mohamed Hadi; Matin, M. A, (IEEE, 2021)
This paper describes the efficient arbitration scheme of an interface that provides access by multiple AMBA processors to targets in SoC (System on the Chip). The arbiter receives requests from several processors and issues grant signals by using its internal arbitration process to that processor allowed to get control over the bus through the AHB interface. The interface is common for all the accessing processors to decide who’s address, control signals, read data and write data to access any specific targets out of many like RAM or registers or others. The HDL modelling was done using Verilog HDL, a simulation by Cadence and Modelsim Simulator, and hardware implementation using Xilinx Pegasus FPGA device. FPGA device is used for quick implementation at its site without going foundry so that its hardware impact can be sorted out. It can be implemented in ASIC (Application Specific Integrated Circuit) too, for low gate count, higher speed low power for any SoC. The processor interface is the significant and critical block determining the controlling mechanism to provide processor access inside slave targets inside any system. A single processor was used previously. But modern systems are very sophisticated in respect of speed, complexity and size. To op the need for a complex system, multiple processors are put in Chip and the arbitration system’s job is to figure out efficient access by several processors. This research addresses efficient multiprocessor access by implementing a smart arbitration mechanism to provide grants to the processors. AMBA bus protocol is the industry-standard protocol and very convenient to use with any off the shelf macro available for the high tech industry.